Characterization of the Phosphotransferase from Bacillus subtilis 1101 That Is Responsible for the Biotransformation of Zearalenone - Yuzhuo Wu; Qiuyu Zhou; Junqiang Hu; Yunfan Shan; Jinyue Liu; Gang Wang; Yin-Won Lee; Jianrong Shi; Jianhong Xu (Toxins)
Bacillus microorganisms play an important role in the zearalenone (ZEA) biotransformation process in natural environments. The phosphotransferase pathway in Bacillus is both widespread and relatively well conserved. However, the reaction kinetics of these phosphotransferases remain poorly understood, and their catalytic activities are suboptimal. In this study, a ZEA phosphotransferase, ZPH1101, was identified from Bacillus subtilis 1101 using genome sequencing. The product transformed by ZPH1101 was identified as phosphorylated ZEA (ZEA-P) through LC-TOF-MS/MS analysis. The experiments conducted on MCF-7 cells demonstrated that ZEA-P exhibited a lower level of estrogenic toxicity than ZEA. The optimal reaction conditions for ZPH1101 were determined to be 45 °C and pH 8.0. The maximum velocity (Vmax), Michaelis constant (Km), and catalytic constant (kcat) were calculated through fitting to be 16.40 μM·s−1·mg−1, 18.18 μM, and 54.69 s−1, respectively. Furthermore, adding 1 mmol/L Fe2+ or Fe3+ to the reaction system increased the efficiency of ZPH1101 in converting ZEA by 100% relative to the system containing solely 1 mmol/L ATP and 1 mmol/L Mg2+, suggesting that low concentrations of Fe2+ or Fe3+ can improve the ZPH1101-mediated transformation of ZEA. This study contributes to the enzymatic removal of ZEA and broadens the spectrum of strain and enzyme options available to researchers for ZEA detoxification efforts.